Comparing the effects of alternate day and daily thyroxine replacement therapy in subclinical hypothyroidism - Mishra, Sanjay; Gupta, Arjit (International Journal of Research in Medical Sciences, 2022)
Background: Subclinical hypothyroidism (SCH) is defined as serum thyroid-stimulating hormone (TSH) level above upper limit of normal despite normal levels of serum free thyroxine. According to recommendations, L-thyroxine treatment for hormone replacement therapy should be continued on daily basis. However, some trials have challenged daily regimen for management of hypothyroidism and have suggested dosage scheduling at weekly, twice-a-week or alternate day as possible alternatives having similar effect as for daily regimen. Methods: Study was prospective randomized cross-over intervention design. Thyroid functions (T3, T4 and TSH) were measured using third generation non-isotopic immunochemiluminescence method using standard protocol. 120 patients with clinically established hypothyroidism were enrolled in study. Results: Difference in mean TSH levels of group I and group II were not found to be statistically significant at baseline (8.247±2.288 mIU/ml versus 8.210±2.650; p=0.935), at 6 weeks (2.337±1.792 mIU/ml versus 2.843±2.410 mIU/ml; p=0.195) and at 12 weeks (2.508±1.180 mIU/ml versus 2.831±1.200 mIU/ml; p=0.191). Difference in mean T3 levels of group I and group II were not found to be statistically significant at baseline (1.118±0.199 ng/dl versus 1.184±0.187 ng/dl; p=0.061), at 6 weeks (1.266±0.295 ng/dl versus 1.196±0.289 ng/dl; p=0.192) and at 12 weeks (1.121±0.211 ng/dl versus 1.179±0.203 ng/dl; p=0.174). Difference in mean T4 levels group I and group II were not found to be statistically significant at baseline (8.422±2.054 µg/dl versus 7.899±2.333 µg/dl; p=0.196), at 6 weeks (8.852±2.836 µg/dl versus 8.533±2.672 µg/dl; p=0.527) and at 12 weeks (8.159±2.235 µg/dl versus 7.990±2.463 µg/dl; p=0.728). Conclusions: The findings of present study show that alternate day L-thyroxine is a viable solution for the management of SCH.